Кримінологічний аналіз стану воєнно-насильницької злочинності проти цивільного населення в контексті збройного конфлікту в Україні - Сокуренко, В.В.; Sokurenko, V.V. (Вісник Луганського навчально-наукового інституту імені Е. О. Дідоренка. - 2024. - Вип. 2, ч. 2. - С. 154-167, 2024)
Стаття присвячена кримінологічному аналізу стану воєнно-насильницької зло-чинності проти цивільного населення в контексті міжнародного збройного кон-флікту в Україні. Встановлено, що частка воєнних-насильницьких злочинів щодо цивільних осіб у загальній структурі воєнно-насильницької злочинності складає при-близно 70% від офіційно зареєстрованих статистичних даних. Апроксимовані розрахунки виявили, що кількість офіційно зареєстрованих воєнно-насильницьких зло-чинів, передбачених ч.1 ст. 438 КК України, проти цивільного населення у 2022 р. склала 42271 кримінальне правопорушення, а у 2023 р. – 42661.З числа зареєстрованих злочинів, передбачених ч.2 ст. 438 КК України, не менше 95% припадає на цивільних осіб. За 2022 р. –це близько 5712 випадків, а у 2023 –1751. Наголошено, що щонайменше кожен четвертий український військовополонений зазнає жорстокого із собою поводження з боку представників російської федерації. Це латентна частина, яка до звільнення з полону лишається в тіні. Аналогічна ситуація складається і з, так званими, «цивільними полоненими», або «цивільними заручниками». Їх приблизна кількість –1600 осіб. Відстоюється думка про те, що подібне поводження із цивільними складає елемент цілеспрямованої державної політики країни-агресора, у зв’язку з чим є підстави кваліфікувати такі дії як злочини проти людяності de lege ferenda та за міжнародним кримінальним правом.

The article is devoted to a criminological analysis of the state of war-violent crime against the civilian population in the context of the international armed conflict in Ukraine. It was established that the share of violent war crimes against civilians in the overall struc-ture of violent war crimes is approximately 70% of officially registered statistical data. Ap-proximate calculations revealed that the number of officially registered violent war crimes provided for in Part 1 of Art. 438 of the Criminal Code of Ukraine, there were 42,271 criminal offenses against the civilian population in 2022, and 42,661 in 2023. From the number of registered crimes, provided for in Part 2 of Art. 438 of the Criminal Code of Ukraine, at least 95% of which are civilians. Among violent war crimes against the civilian population, according to judicial prac-tice, cruel treatment in the form of threats of intentional murder, infliction of bodily harm, torture and illegal deprivation of liberty prevail (74%). 20.4% of these crimes are combined with intentional homicide (Part 2 of Article 438 of the Criminal Code of Ukraine). Sexual violence related to armed conflict accounts for 5.6%. The predominance of civilians among the victims is due to their increased victimhood, vulnerability, and insecurity in the face of representatives of the occupation forces. At the same time, these data do not cover the latent part. It is emphasized that at least every fourth Ukrainian prisoner of war is brutally treated by representatives of the Russian Federation. This is a latent part that remains in the shad-ows until release from captivity. Approximated number of «civilian prisoners» or «civilian hostages» is 1,600 people. It is argued that such treatment of civilians is an element of the targeted state policy of the aggressor country, which is why there are grounds to classify such actions as crimes against humanity de lege ferendaand under international criminal law.

Статья посвящена криминологическому анализу состояния военно-насильственной преступности против гражданского населения в контексте международного вооруженного конфликта в Украине. Установлено, что доля военно-насильственных преступлений в отношении гражданских лиц в общей структуре военно-насильственной преступности составляет примерно 70% от официально зарегистрированных статистических данных. Аппроксимированные расчеты обнаружили, что количество официально зарегистрированных военно-насильственных преступлений, предусмотренных ч.1 ст. 438 УК Украины против гражданского населения в 2022 г. составило 42271 уголовное правонарушение, а в 2023 г. – 42661. Из числа зарегистрированных преступлений, предусмотренных ч.2 ст. 438 УК Украины, не менее 95% приходится на гражданские лица. За 2022 г. – это около 5712 случаев, а в 2023 –1751. Отмечено, что по меньшей мере каждый четвертый украинский военнопленный испытывает жестокое обращение со стороны представителей российской федерации. Это латентная часть, которая до освобождения из плена остается в тени. Аналогичная ситуация складывается и с, так называемыми, «гражданскими пленными», или «гражданскими заложниками». Их примерное количество –1600 человек. Отстаивается мнение о том, что подобное обращение с гражданскими является элементом целенаправленной государственной политики страны-агрессора, в связи с чем есть основания квалифицировать такие действия как преступления против человечности de lege ferenda и по международному уголовному праву.
Criminology analysis of violent war crimes againstthe civilian populationin the context of the armedconflict in Ukraine
Keywords: кримінологічний аналіз; війна; збройний конфлікт; воєнно-насильницька злочинність; цивільні особи; рівень; динаміка; структура; латентність; criminological analysis; war; armed conflict; violent war crime; civilians; level; dynamics; structure; latency; криминологический анализ; война; вооруженный конфликт; военно-насильственная преступность; гражданские лица; уровень; динамика; латентность